Designing Educational Buildings and Learning Centers through Digital Technologies and Artificial Intelligence: The Role of Color Selection - Madinabonu, Siddiqova (EDUMALSYS Journal of Research in Education Management, 2025)
This article explores the strategic role of color in the interior design of educational institutions, with particular emphasis on the integration of digital technologies and artificial intelligence (AI) to create color schemes that align with the psychophysiological characteristics of learners. Set within the context of Uzbekistan’s transition to a digital economy, the study highlights how AI-driven tools are being increasingly used in education to enhance the effectiveness and comfort of learning environments. Drawing from national construction standards and age-specific psychological research, the study investigates how color influences student motivation, concentration, memory retention, and emotional well-being. The article outlines a step-by-step approach to AI-assisted educational center design, covering aspects from data collection and analysis to personalization of learning spaces. The findings emphasize the importance of interdisciplinary collaboration between educators, designers, technologists, and psychologists in shaping adaptive, student-centered educational environments. Ultimately, the integration of aesthetics, cognitive science, and digital innovation is shown to enhance both the visual and functional quality of learning spaces, contributing to improved educational outcomes.